Advances in immunotherapy for mucosal melanoma: harnessing immune checkpoint inhibitors for improved treatment outcomes - Shan, Zexing; Liu, Fei (Frontiers in Immunology, 2024)
Mucosal melanoma (MM) poses a significant clinical challenge due to its aggressive nature and limited treatment options. In recent years, immunotherapy has emerged as a promising strategy for MM, with a particular focus on immune checkpoint inhibitors such as PD-1 and CTLA-4 inhibitors. These inhibitors have demonstrated substantial efficacy by harnessing the body's immune response against tumors. Moreover, adoptive cell transfer (ACT), anti-angiogenic therapy, and combination therapies have garnered attention for their potential in MM treatment.ACT involves modifying T cells to target melanoma cells, showing promising antitumor activity. Anti-angiogenic therapy aims to impede tumor growth by inhibiting angiogenesis, while combination therapies, including immune checkpoint inhibitors and targeted therapies, offer a multifaceted approach to overcome treatment resistance. This comprehensive review explores the advancements in immunotherapy for MM, highlighting the role of diverse therapeutic modalities in enhancing treatment outcomes and addressing the challenges posed by this aggressive malignancy.